2023
DOI: 10.1108/ijpdlm-09-2021-0396
|View full text |Cite
|
Sign up to set email alerts
|

Alternative certification system for supply chain sustainability: how stakeholder alignment affects institutionalization

Abstract: PurposeThis study expands the isomorphic logic on the participatory guarantee system (PGS) alternative certification method, which aims to level the supply chain sustainability field to determine how the alignment of disadvantaged agrifood stakeholders (e.g. small/applicant farmers, local organizations, consumers and volunteer auditors) might neutralize the negative effects of stakeholder heterogeneity (SH) on PGS recognition.Design/methodology/approachThe sample comprised 113 multilateral matching questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 66 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Recommendations regarding some of the inferred challenges already exist in the literature, such as for the challenge of untrustworthy certifications (C9) (e.g. Liu, 2023) and insufficient sustainability performance (C3) (e.g. Yun et al, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendations regarding some of the inferred challenges already exist in the literature, such as for the challenge of untrustworthy certifications (C9) (e.g. Liu, 2023) and insufficient sustainability performance (C3) (e.g. Yun et al, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Furthermore, there is a missing link between issues mentioned in practical GSCDDA discourses and theoretical SSCM developments, which inhibits establishing synergies between these streams. For instance, there is a missing link between theoretical SSCM developments regarding certifications (Liu, 2023) and the issue of untrustworthy certifications often mentioned in the GSCDDA discourse. To address these research gaps, we pose the following research questions (RQs): RQ1: Which SSCM stakeholder groups, challenges and opportunities exist in the GSCDDA discourse, and how do these components interrelate?…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a survey was carried out with marginalised stakeholders from the Green Conservation Label managed by Taiwan's Tse-Xin Organic Agriculture Foundation (TOAF) on social sustainability in the supply chain. Liu (2023) observed that disadvantaged stakeholders mobilised a pool of resources to establish alternative institutions. The study provides recommendations to managers and policy makers for decision-making related to agriculture.…”
Section: The Challenge Of Inclusiveness As Transformative Practicesmentioning
confidence: 99%
“…The triple-bottom-line concept, which addresses business, social, and environmental aspects, serves as a framework for defining sustainability in supply chain management (Seuring and M€ uller, 2008;Yosef et al, 2023). Confirming and verifying that products, processes, and activities in the supply chain adhere to specific sustainability requirements and certifications is a crucial strategic and competitive concern for sustainability in supply chains (Grimm et al, 2016;Liu, 2023) Throughout history, fraud has taken place with severe repercussions. Fraud is a general phrase that refers to the purposeful and planned act of incorporating, removing, altering, or distorting of products or services offered for sale as well as the making of false or deceptive statements about a good or service to obtain financial advantage (Spink and Moyer, 2011;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…, 2023). Confirming and verifying that products, processes, and activities in the supply chain adhere to specific sustainability requirements and certifications is a crucial strategic and competitive concern for sustainability in supply chains (Grimm et al ., 2016; Liu, 2023)…”
Section: Introductionmentioning
confidence: 99%